Hedging Performance of Indonesia Exchange Rate - Eneng Nur Hasanah (Universitas Islam Bandung, 2018)
The fluctuation of exchange rate very given the impact to the situation of Indonesia economic, it will give impact to the economics of Indonesia, with the case, this paper examines the hedging ratio performance by using The Constant Conditional Correlation (CCC) of Bivariate Generalized Autoregressive Conditional Heteroscedasticity (BGARCH). The result of hedging ratio performance of Indonesia exchange rate is very low, it means that Indonesia almost never mitigate Rupiah (IDR).